The psychology of sarcastic discourse in ancient Algerian literature Ibn Mahrez Al-Wahrani as a Sample - ELMILOUD, KARDAN (International Journal of Psychosocial Rehabilitation, 2022)
sarcasm is a psychological phenomenon within a dynamic and changing social framework, so the production of satirical discourse actually expresses a psychological secrets centered in the productive self, and in all of this it is the result of multiple reasons and factors, and as Arabic literature has preserved for us poetic and prose names in the field of irony, such as Abu Al-Ala Al-Maarri and Bashar Ibn Bard and Badi’ al-Zaman al-Hamadhani, the ancient Algerian literature records a name that is no less important than these, and we mean Rukn al-Din Ibn Mahrez al-Wahrani.Who isIbn Mahrez al-Wahrani? What are the manifestations of satirical discourse in its literary impact? What are the reasons and motives for that?